Fragmented Politics and Public Debt - Crivelli, Ernesto (IMF Working Papers; Working Paper ;, 2016)
In this paper, we study the impact of fragmented politics on public debt-in particular, between two consecutive legislative elections. Using data for 92 advanced and developing countries during 1975-2015, we find a positive association between political fragmentation and public debt changes. Corruption magnifies the effects; with higher perceived corruption, political fragmentation has a bigger sway on debt increases. The influence of political fragmentation on debt dynamics is somewhat asymmetric, with larger and more significant effects during periods of debt reduction. Establishment of fiscal councils helps attenuate the negative impact of political fragmentation on public debt dynamics.